ANALISIS KELAYAKAN NASABAH DALAM PEMINJAMAN DI BPR OPHIR UJUNG GADING PASAMAN BARAT - Sahrawani Sahrawani; Maisarah Leli; Fawza Rahmat (STAI YAPTIP, 2023)
This research explains the proplem of whether there is an influence ofpromotions on the interest in saving of the people of Situak Barat at the shariapeople’s Financing (BPRS) Mentari Pasaman Saiyo Ujung Gading. This researchaims to partially test how promotion influences interest in saving and how muchinfluence promatiaon has on interest in saving in West Siak society at BPRSUjung Gading. After this research is carried out, it is hoped that it will providebenefits for several parties, including providing input from information on thepractice of sharia banking, especially marketing managers in determining themost effective promotional policies to recruit savings Customers at BPRS ujunggading.In this research, the research methodology used is a method asosiatif cacualwith a quatitative type of research. The respondents in this study were 30responden with 14 statements, namely the west siak community. Samplingtechniques using samples rondom sampling, data collection techniques usinginterviews, questionnaires and documentation as well as data analysis techniquesused in this thesis are Validity test, Reability test, Normality test, Simultaneoustest(F) and Partial test(T). The research results show that there ia a positiveinfluence berween the promation variabel(X) and the interest in savingvariable(Y), Seen from the regression equation that has been generated usingSPSS. Namely the magnitude of the influence of promation(X) on the interest insaving(y) of the west siak community at BPRS MPS ujung gading.